Understanding the behavior of l-type flange joint in wind turbine towers: Proposed mechanisms. (December 2022) - Tran, Thanh-Tuan; Lee, Daeyong
Graphical abstract: Highlights: Theoretical models of first yielding points at the bolt and flange-to-shell junction are recommended. Formulas for calculating the plastic tensile resistance at the yielding stage are proposed. A decision tree, which presents the possible failure states of a bolted flange joint, is developed. Satisfactory prediction is verified against three available flange joints. Abstract: Generally, collapses of wind turbine towers are caused by bolt ruptures or flange separations at ring flange joints; it is therefore imperative to identify the failure characteristics of bolted ring flange joints. In practical design, traditional approaches primarily focus on bolt failure without paying attention to bolt bending. To handle this limitation, this study aims to examine all possible failure mechanisms of the l -type flange joint used in wind turbine towers. Two independent yielding cases (i.e. yielding in the bolt and yielding in the flange-to-shell junction) and the corresponding plastic tensile resistance are proposed. Numerical simulations of three available l -type flange joints are implemented to verify the accuracy and efficiency of the proposed mechanisms. This study provides a value design framework to predict the load-carrying capacity of flange joints. Combined with existing failure modes, a decision tree that presents possible failure states for bolted flange joints is developed.